2001
DOI: 10.21273/hortsci.36.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Leachate from Earthworm Castings Breaks Seed Dormancy and Preferentially Promotes Radicle Growth in Jute

Abstract: Seeds of jute (Chorchorus olitorius L.) undergo a period of dormancy, which hitherto has been broken with the conventional method of steeping in boiling water. Another seed treatment procedure, which involves soaking seeds in earthworm cast leachate, was found superior to the conventional method of breaking dormancy. Furthermore, radicle growth was enhanced when seeds were irrigated with water that contained earthworm cast leachate instead of water without earthworm cast leac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…As indicated in Fig. 6, earthworms affect four of seven life stages directly (survival of post‐dispersal seed predation: Grant 1983, Thompson et al 1994, storage in soil: Thompson et al 1994, germination: Ayanlaja et al 2001 and seedling survival: Lee 1985) reflecting the capacity of earthworms to drive plant recruitment and plant community composition. Surprisingly, the majority of the previous studies concentrated on indirect effects of earthworms on plants (reviewed by Scheu 2003, Brown et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in Fig. 6, earthworms affect four of seven life stages directly (survival of post‐dispersal seed predation: Grant 1983, Thompson et al 1994, storage in soil: Thompson et al 1994, germination: Ayanlaja et al 2001 and seedling survival: Lee 1985) reflecting the capacity of earthworms to drive plant recruitment and plant community composition. Surprisingly, the majority of the previous studies concentrated on indirect effects of earthworms on plants (reviewed by Scheu 2003, Brown et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Surface‐foraging species such as Lumbricus terrestris are effective in burying seeds, while the surface casts produced by many species often contain seeds (McRill and Sagar 1973, Grant 1983, Thompson et al 1994, Milcu et al 2006). Thereby, earthworms may affect seedling establishment by a variety of mechanisms, through selective ingestion and digestion of seeds (McRill and Sagar 1973, Shumway and Koide 1994, Eisenhauer 2008), downward or upward seed transport (Grant 1983, Eisenhauer et al 2008) and acceleration (Ayanlaja et al 2001, Eisenhauer 2008) or delaying of seed germination (Grant 1983, Decaens et al 2001). A grassland field study by Thompson et al (1994) indicated that the composition of seeds in bulk soil and earthworm casts differ; seeds in earthworm casts were substantially smaller (<0.3 mg) than the majority of plant seeds of the soil seed bank (0.3–1 mg).…”
mentioning
confidence: 99%
“…2003). Selective ingestion and digestion of seeds (McRill & Sagar 1973; Shumway & Koide 1994); downward or upward seed transport (Hurka & Haase 1982; Grant 1983); acceleration (Ayanlaja et al . 2001); or delaying seed germination (Grant 1983; Decaens et al .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, physicochemical and microbiological properties are closely interlinked and contribute together to nutrient cycling in casts (Brown et al, 2000;Scheu, 1987;Sheehan et al, 2008). On a larger scale, the impact of such soil-earthworm interactions on cast properties should be better describe to predict the subsequent effects on seed germination, seedling and plant growth (Ayanlaja et al, 2001;Decaëns et al, 2003;Forey et al, 2011;Scheu, 2003). A better understanding of the way earthworm effects on cast properties depend on soil type would help predict the effects of invasive earthworms on natural habitats (Hendrix and Bohlen, 2002).…”
Section: Resultsmentioning
confidence: 99%